1990
DOI: 10.1038/sj.bdj.4807295
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of clinically undetected occlusal dentine caries in Scottish adolescents

Abstract: During the third examination of a 3-year anti-caries dentifrice study, bitewing radiographs were read to detect occlusal, as well as approximal caries lesions in 2623 subjects aged 14-15 years. These analyses showed that 1.4% of 2107 upper molars and 7.2% of 2288 lower molars (P less than 0.001), previously scored as clinically 'sound', were carious at a radiographic Grade '3' score (dentinal involvement), and 0.2% had radiographic pulpal lesions. However, for teeth which had been deemed as having a 'suspicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
6

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 0 publications
2
50
0
6
Order By: Relevance
“…5 It was concluded that, even with a trained clinical examiner and optimum conditions, hidden caries was a major problem when no radiographs were exposed. While there is some risk to patients and staff when using ionising radiation, this risk can be reduced through proper training, use of appropriate films and radiographic equipment, and continued professional development to ensure radiation protocols are up-to-date and being implemented efficiently.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…5 It was concluded that, even with a trained clinical examiner and optimum conditions, hidden caries was a major problem when no radiographs were exposed. While there is some risk to patients and staff when using ionising radiation, this risk can be reduced through proper training, use of appropriate films and radiographic equipment, and continued professional development to ensure radiation protocols are up-to-date and being implemented efficiently.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…12 Clinically undetected occlusal caries has been reported by a number of authors. 13,14 With the decrease in caries incidence in some geographical areas, occlusal caries beneath pits and fissures now forms a higher proportion of the total caries experience so that 'hidden caries' beneath intact surfaces has come into prominence, attracting the names fluoride syndrome and fluoride bomb. 15- 18 Weerheijm et al found in a group of 6-18 year olds that 15 per cent of the first and second molars judged clinically sound exhibited bite-wing radiolucencies and that these hidden lesions occurred in children with low DMF scores."…”
Section: Introductionmentioning
confidence: 99%
“…59 The terms 'hidden caries' or 'occult caries' refer to the fact that such lesions are thought to have originated as carious lesions, and have eluded discovery during clinical examination. [60][61][62][63] On the other hand, the terms 'fluoride bombs' or 'fluoride syndrome' suggest that fluoride is an aetiological factor 64,65 (Fig 7a). This theory states that fluoride has encouraged remineralization and the slowing of caries process in the surface enamel, masking the cavitation which progresses in dentine.…”
mentioning
confidence: 99%